Juvenile ossifying fibroma of the mandible: A case report (Indian Journal of Case Reports, 2019)
Juvenile ossifying fibroma (JOF) is a rare fibro-osseous entity of the craniofacial skeleton, which poses diagnostic and therapeutic difficulty due to its characteristic behavioral, clinical, and histopathological features. The maxillary involvement of the lesion leads to, nasal obstruction, epistaxis and exophthalmos. The tumor very rarely involves mandible and only a few cases have been reported. It shows slight male predilection with age ranging from 2- 15 years has been reported. Here, we report the case of juvenile ossifying fibroma which came to the department with a chief complaint of swelling in the lower right side of the face since three months. After obtaining the final histopathological diagnosis, the lesion was treated with surgical excision.